2014
DOI: 10.2139/ssrn.2445001
|View full text |Cite
|
Sign up to set email alerts
|

Skills and Youth Entrepreneurship in Africa: Analysis with Evidence from Swaziland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
4
39
0
3
Order By: Relevance
“…Compared to Western societies, social norms and customs in many emerging nations discriminate against women (Ghosh & Cheruvalath, ) and limit their opportunities for education and skills development. For young African entrepreneurs looking for business opportunities, possessing the required technical and managerial skills is critical for success, and the benefit of providing relevant training to prospective entrepreneurs outweighs that of giving them financial subsidies (Brixiova, Ncube, & Bicaba, ; Sackey, Faltholm, & Ylenenpaa, ). In a study that compared success factors and problems faced by entrepreneurs in Ghana, Kenya, and Nigeria, Benzing and Chu () found that having managerial and customer service skills was critical for success.…”
Section: Research On Female Entrepreneurshipmentioning
confidence: 99%
“…Compared to Western societies, social norms and customs in many emerging nations discriminate against women (Ghosh & Cheruvalath, ) and limit their opportunities for education and skills development. For young African entrepreneurs looking for business opportunities, possessing the required technical and managerial skills is critical for success, and the benefit of providing relevant training to prospective entrepreneurs outweighs that of giving them financial subsidies (Brixiova, Ncube, & Bicaba, ; Sackey, Faltholm, & Ylenenpaa, ). In a study that compared success factors and problems faced by entrepreneurs in Ghana, Kenya, and Nigeria, Benzing and Chu () found that having managerial and customer service skills was critical for success.…”
Section: Research On Female Entrepreneurshipmentioning
confidence: 99%
“…The benefits of TVET in terms of earning and social promotion vary across countries and influence its attractiveness. Brixiová et al, (2014) researched youth employment in Africa and came up with new evidence on the effects of policies in Swaziland during 2007-2010. They carried out a multinomial logit regression analysis to analyze the socioeconomic drivers of the unfavorable youth labor market outcomes on the supply side.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…In the context of Africa, educational attainment, perceived knowledge and skills and opportunity recognition skills are more likely to facilitate entry into entrepreneurial activity (Brixiová, et al, 2015;Cetindamar et al, 2012). SA serves as unique exemplar with resources that are not possessed by many countries.…”
Section: Gender Gap In Entrepreneurshipmentioning
confidence: 99%
“…African countries are increasingly recognising entrepreneurship as a vehicle their citizen can use to create jobs, foster economic development and growth while reducing poverty (Amin, 2010;Brixiová et al, 2015). But, the disproportionate engagement in entrepreneurship activities between men and women in both developing and developed economies require investigating .…”
Section: Introductionmentioning
confidence: 99%